FIRST ORDOVICIAN SPONGE FROM THE PUNA REGION, NORTHWESTERN ARGENTINA (Ameghiniana, 2014)
The first Ordovician sponge discovered from the Puna region is described and figured. A single specimen of a hexactinellid sponge, Larispongia magdalenae new genus and species, has been collected from vo1caniclastic rocks of the Las Vicuñas Formation (Tremadocian) in Lari Creek, southwest of the Salar del Rincón area, Salta province, Argentina. Larispongia magdalenae is included in the Family Pelicaspongiidae based on its irregular and thick walled skeleton, and on the differentiated large and smooth hexactines on dermal and gastral surfaces, not arranged into a quadrate pattern. Larispongia is readily differentiated from the other genera of the family, by its uniformly shaped and smooth hexactines, thin parieties that separate adjacent openings, and densely packed arrangement of the openings.